2010
DOI: 10.2527/jas.2008-1755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fixed sources of variation and estimation of genetic parameters for incidence of bovine respiratory disease in preweaned calves and feedlot cattle12

Abstract: The primary objective of this study was to estimate variance components and heritability of bovine respiratory disease (BRD) incidence in beef calves before weaning and during the finishing phase. The second objective was to investigate the impact of BRD incidence and treatment frequency on performance and carcass traits. Bovine respiratory disease is the biggest and most costly health challenge facing the cattle industry. The 2 populations used consisted of 1,519 preweaned calves and 3,277 head of feedlot cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 13 publications
1
34
1
Order By: Relevance
“…Presented in Table 4 are previously reported heri tability estimates for BRD, cortisol, total IgG, IgG1, and IgG2 for comparison with those reported in this study. Previous heritability estimates for BRD confirm the estimate (h 2 = 0.17 ± 0.08) in the current research (Snowder et al, 2005(Snowder et al, , 2006(Snowder et al, , 2007Schneider et al, 2010). It is possible that heritability estimates reported in this study were inflated due to dominance; however, given the structure of the data and the unknown breed composition of the dam, these effects were unable to be accounted for.…”
Section: Applicability Of Results To Us Beef Industrysupporting
confidence: 83%
“…Presented in Table 4 are previously reported heri tability estimates for BRD, cortisol, total IgG, IgG1, and IgG2 for comparison with those reported in this study. Previous heritability estimates for BRD confirm the estimate (h 2 = 0.17 ± 0.08) in the current research (Snowder et al, 2005(Snowder et al, , 2006(Snowder et al, , 2007Schneider et al, 2010). It is possible that heritability estimates reported in this study were inflated due to dominance; however, given the structure of the data and the unknown breed composition of the dam, these effects were unable to be accounted for.…”
Section: Applicability Of Results To Us Beef Industrysupporting
confidence: 83%
“…Unlike commercial feedlots, where sorting of cattle by weight to provide uniform lots at slaughter is common, in our study, steers remained in the same pen for the duration of the feeding period. In a survey of 3277 feedlot cattle, incidence of BRD was estimated at 9.43% (Schneider et al 2010), substantially higher than the 0.4 to 3.5% observed in the present study. The incidence of treatment for bloat in the present study (2 to 5%) would likely have been reduced if ionophores had been included in the diet (Galyean and Rivera 2003), but the presence of monensin in diets would have confounded the observed responses to the other subtherapeutic antimicrobials administered.…”
Section: Animal Healthcontrasting
confidence: 41%
“…It has also been demonstrated that stressed calves, nervous animals and some breeds are more susceptible to BRD (Fell et al, 1999;Snowder et al, 2006;Cusack et al, 2007;Stilwell et al, 2008c;Pereira and Stilwell, 2011). Resistance to BRD also has a genetic component, although heritability seems to be small (Schneider et al, 2010). "Bullers" (hierarchal lower animals that are constantly harassed by pen mates) are 2.5 times more likely to have respiratory disease and 3.2 times more likely to die (Taylor et al, 1999(Taylor et al, , 2010.…”
Section: Bovine Respiratory Diseasementioning
confidence: 99%